El concepto liberal en la consolidación de un nuevo orden político en la República de Colombia (1819-1831) - Kevin Ramírez (Nuevo mundo - Mundos Nuevos)
This article analyzes the intersection of the concepts of "liberal" and "order" during the formation, crisis, and dissolution of the First Republic of Colombia, highlighting their role in legitimizing the political projects. From a conceptual perspective, it explores how these polysemic and contested terms shaped political discourse and institutional processes of the new republic.The first section examines the Congress of Cúcuta in 1821, where, despite the intention to establish a liberal government, priority was given to an order that would guarantee independence and stability. The second section addresses the 1826 crisis, during which tensions between constitutional order and local demands generated alternative proposals, such as the Bolivian Constitution. The third section analyzes the tensions between liberty and order during the Bolivarian dictatorships, emphasizing how political factions used these concepts to legitimize their positions. Finally, it explores how the creation of new republics was driven by the establishment of orders based on liberal institutions.The article concludes that the relationship between "liberal" and "order" was both convergent and conflicting, reflecting the complexities of republican construction and the struggle for legitimacy in a context of political and social transformation.